Basal cell carcinomas in a tertiary referral centre: a systematic analysis. (1st November 2014) - Dreier, J.; Cheng, P.F.; Bogdan Alleman, I.; Gugger, A.; Hafner, J.; Tschopp, A.; Goldinger, S.M.; Levesque, M.P.; Dummer, R.
Summary: Background: Basal cell carcinoma (BCC) is the most frequent skin cancer with increasing incidence and generally high cure rates. BCC can be quite aggressive and is difficult to treat. Objectives: To investigate BCCs with a focus on histological subtypes, treatment procedures and correlation to clinical progress to collect further information on complex BCC cases. Methods: In this retrospective single‐centre analysis the dermatopathology database, a network of cooperating dermatological surgeons, was queried for BCC cases between January 2007 and December 2011. Of 14 423 samples from a total of 9652 patients initially identified, 2938 patients were treated at the University Hospital Zurich and had corresponding local electronic patient records. Results: Patients ( n = 2938) (with 4769 diagnoses, 2006 re‐excisions with 1180 microscopically controlled surgeries) were classified based on severity estimations into 2240 simple, 640 moderate, and 58 severe cases, including one BCC‐treatment‐associated death and 11 patients with subsequent participation in a clinical trial. In moderate and severe cases ( n = 698), there were significantly higher rates of unique histological diagnoses ( n = 2·5; P < 0·0001), higher association with basosquamous carcinoma [odds ratio (OR) 3·6; P < 0·0001] and sclerosing BCC (OR 2·48; P < 0·0001). Of the patients with basosquamous carcinoma 82·6% had a previous history of BCC. Conclusions: This is the first study that analyses the frequency of complicated BCCs in a tertiary referral centre. There were 6·6% moderate (640 of 9652) and 0·6% (58 of 9652) severe cases. We found significantly more varying histological diagnoses and significant association with aggressive subtypes in moderate and severe cases. These patients might especially benefit from new therapeutic options.